Studies on Angiotensin-Converting Enzyme Insertion/Deletion Polymorphism and Genotype Distributions in Turkish Preeclampsia Patients - Ceyhun Bereketoğlu; Mülkiye Kasap; Ayfer Pazarbaşı (Hindawi Limited, 2012)
Placental, immune and genetic factors are thought to play an important role in preeclampia (PE)'s pathophysiology. Angiotensin-Converting Enzyme (ACE) plays a vital role in the renin-angiotensin-system (RAS) which regulates blood pressure by converting angiotensin I into a powerfull vasoconstrictor angiotensin II. A deletion polymorphism (D allele) has been reported to be associated with elevated ACE activity. The aim of the this study was to investigate whether there is an association between angiotensin converting enzyme (ACE) insertion/deletion (I/D) polymorphism and PE. In this study, 120 preeclamptic and 116 normotensive Turkish pregnant women were genotyped for ACE I/D polymorphism and the distribution of genotype and allele frequencies of this polymorphism in preeclampsia and controls were evaluated. Codominant, dominant and recessive models were appplied in ACE gene I/D polymorphism. In the codominant model, DD genotype was found significantly more frequent in preeclampsia than controls (P=0.016). Moreover, in dominant model (DD frequency versus DI+II frequency) there was a significant relation between DD genotype and preeclampsia (P=0.006). D allele frequency was 64.6% in preeclampsia while it was 56.1% in controls (P=0.062). In conclusion, there was significant difference in genotype distribution between preeclampsia and controls.